Peran Kehumasan dalam Organisasi Pedesaan - Andini Dwi Jayani; Aulia Fatminadila; Eka Susanti Simalango; Ahmad Arya Ardhana; Erwan Effendi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Examining the function of public relations ethics in village organizations. Public Relations plays an important role in the current era of open access to information, especially in the Village Government environment. The government is expected to be able to manage information in each agency and be able to improve services. Researchers used documentation, observation and interview techniques as well as qualitative descriptive methods to collect data for this research. Each village official should ideally play the role of village public relations or information and documentation manager, whose task is to convey information to the community in an open and easy-to-understand manner.